Cold storage of "dedo-de-moca" 'BRS Mari' pepper in polymeric packaging Armazenamento refrigerado de pimenta dedo-de-moca 'BRS Mari' em embalagem polimérica - Soethe C.* (2017)
The objective of this work was to evaluate if there is difference between polyethylene terephthalate (PET) and polyvinyl chloride (PVC) packaging on the quality, maintenance and the effect of storage time on the maintenance of the physical and chemical characteristics, the content of bioactive compounds and antioxidant activity in cold stored 'BRS Mari' hot pepper. Fruits were harvested at 80 days after anthesis (DAA). The treatments evaluated were PVC and PET packing combined with six storage times (0, 3, 6, 9, 12 and 15 days). 30 peppers were placed in each package. Fruits were stored at 10±1°C and, after each storage time, analyzed for color (h, brightness and chroma), antioxidant activity and soluble solids (SS), titratable acidity (TA), SS/TA ratio, total phenolic and capsanthin. There was no substantial difference between the evaluated packages for the variables analyzed. The storage time had no effect on the soluble solids content, titratable acidity, SS/TA ratio and capsanthin content. The brightness decreased and the value of the hue angle and chroma increased on the third day of storage. The total phenolic content and antioxidant activity decreased on the third day of storage. There were no differences between the PVC and PET packaging on the maintenance of quality and functional properties. The cold storage did not change the taste characteristics, but on the third day of storage the 'BRS Mari' hot peppers showed impaired fruit appearance and reduction of total phenolic content and antioxidant activity.